Effects of contrast cryolipolysis on flank region adiposity: Case study. (23rd September 2018) - Meyer, Patrícia Froes; Consulin, Márcia Cristina Dias; Rodrigues, Thais; Pereira, Aline Marques; Lopes, Patrícia Carolina Martinez; da Silva, Rodrigo Marcel Valentim; de Vasconcellos, Liliane Santos
Summary: Background: The Contrast Cryolipolysis is a non‐invasive technique that aims to reduce localized adiposity with its heating‐cooling‐heating method, resulting in a 45% fat loss in the treated area, with no damage to the skin. Objective: To investigate the effects of contrast cryolipolysis compared to conventional cryolipolysis on localized adiposity. Materials and Methods: This is a case study was carried out with two volunteers. The cirtometry, ultrasonography, and the anthropometric characteristics' analyses of volunteers were performed before and after the intervention. The right flank region underwent conventional cryolipolysis, and the left flank underwent contrast cryolipolysis. Results: The procedures performed in both volunteers had positive results. However, the use of Contrast Cryolipolysis promoted greater loss of adipose tissue, reducing perimetry and cirtometry measurements, as well as the adipose tissue thickness, acknowledged via ultrasonography. Conclusion: The contrast cryolipolysis promotes greater localized adiposity reduction than the conventional cryolipolysis.